QARD-AL-HASSAN AS A TOOL FOR POVERTY ALLEVIATION: A CASE STUDY OF THE FAEL KHAIR WAQF PROGRAM IN BANGLADESH - Farah Muneer; Foyasal Khan (Journal of Islamic Monetary Economics and Finance, 2019)
The central focus of the Islamic economic system is on socioeconomic justice and the overall welfare of society, especially at the bottom of the pyramid segment. Qard-al- Hassan, alongside zakat and sadaqah, is one of the instruments for the redistribution of income and wealth from the rich to the poor in Islam. In 2007, Bangladesh was struck by super cyclone SIDR, leaving 3,406 people dead. Moreover, SIDR caused unprecedented damage to homes, crops and livelihoods. The Fael Khair Waqf (FKW) Program came as a response to the urgent need to assist the victims of the cyclone and initiated an interest-free micro-loan (Qard-al-Hassan) scheme to restore the livelihoods of a large segment of the victims and to lift them out of poverty. While investigating the effectiveness of Qard-al-Hassan in poverty reduction, this paper also examines the FKW program as a case study. Analysis was conducted of 1600 households using an independent sample t-test and logistic regression to investigate to what extent the program has been effective in reducing poverty. The findings of the logistic analysis are that the probability of being poor for FKW participants is around 1.46 times lower than for non-participants. Moreover, the Qard-al-Hassan of FKW lowers the cost of borrowing significantly and hence participants can accumulate more assets, which might help them to improve their economic status. Overall, the effectiveness of the program implies that development practitioners and researchers should promote the outreach of Qard-al-Hassan so that the extreme poor can easily avail themselves of the services.